N-LEVEL AND N-UPPER LEVEL SOFT SETS (FUDMA JOURNAL OF SCIENCES, 2023)
In this paper, the concept of n-upper level soft set is introduced together with some of its properties. It is shown that some properties holding in n-level soft set do not hold in n-upper level soft set. It is further demonstrated that both the first and the second decomposition theorems fails in n-upper level soft set
Keywords: Soft set, Multiset, Soft multiset, n-level Soft set, n-upper level Soft set